Invariant natural killer T cells: Not to be ignored in liver disease. Issue 3 (18th February 2021) - Gan, Jian; Mao, Xiao Rong; Zheng, Su Jun; Li, Jun Feng
Abstract : The liver is an important immune organ. Hepatocellular injury can be caused by many factors, which further leads to chronic liver diseases by activating the immune system. Multiple immune cells, such as T lymphocytes, B lymphocytes, natural killer cells (NKs), natural killer T cells (NKTs), and γδT cells, accumulate and participate in the immune regulation of the liver. NKTs are an indispensable component of immune cells in the liver, and invariant natural killer T cells (iNKTs) are the main subpopulation of NKTs. iNKTs activated by glycolipid antigen presented on CD1d secrete a series of cytokines and also act on other immune cells through cell‐to‐cell contact. Studies on the relationship between iNKTs and liver immunity have provided clues to uncover the pathogenesis of liver diseases and develop a promising strategy for the diagnosis and treatment of liver diseases. Abstract : The liver is the largest parenchymal digestive gland in the body. Innate lymphocytes, including both conventional and unconventional T cells, are abundant in the liver and participate in immune regulation. In addition, multiple types of nonparenchymal cells take on the roles of antigen‐presenting cells in the liver. Therefore, the liver is a potential immune organ, and has important immunomodulatory functions in humans and rodents.